As categorias conceituais (con)formadoras do léxico: progresso, evolução, civilização, raça e mestiçagem em Manoel Bomfim, Oliveira Vianna e Alberto Torres - Stêfany Sidô Ventura (2018)
This work aims at analyzing the (con)formation of the lexicon, systematized by the conceptual categories, progress, evolution, civilization, race and miscegenation in the composition of a conceptual corpus used in the Brazilian socio-historical analysis between the final decades of the 19th century and the beginning of the 20th century. The need to describe, organize and classify society stimulates the creation of terms and concepts that are explanatory of reality. From the 19th century, scientism influenced the studies and analysis of human societies. Great minds and scholars aimed at understanding the historical and social context from a scientific, universalist and staggered view of societies. From this, the Brazilian intellectual production of the time, focused on apprehending and interpreting Brazilian society, its formation process, the results of historical experiences and the possibilities for the future. In this way, the sources of this work, Manoel Bomfim, A América Latina males de origem (1993) e O Brasil (1940) A organização nacional (1978) and O problema nacional brasileiro (1978) by Alberto Torres; Ensaios inéditos (1991) and Populações meridionais do Brasil (2002) by Oliveira Vianna, are designed to systematize the historiographical production of Brazil (from the late nineteenth and early twentieth century) based on the use of a theoretical-conceptual corpus common form conformed by the conceptual categories progress, evolution, civilization, race and miscegenation.